2022
DOI: 10.3389/fnut.2021.795068
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Malnutrition on Contrast-Associated Acute Kidney Injury in Young and Old Patients Undergoing Percutaneous Coronary Intervention: A Multicenter Prospective Cohort

Abstract: BackgroundThe relationship between malnutrition and the risk of contrast-associated acute kidney injury (CA-AKI) and the resulting prognosis in patients undergoing percutaneous coronary intervention (PCI) is still not well known.MethodsPatients undergoing PCI were consecutively enrolled in a multicenter study in China (NCT01402232), categorized by nutritional status (non-malnutrition, malnutrition) based on two different cut-off values (i.e., traditional threshold and the best cut-off value based on the receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The population of the original studies was mainly from China [ 10 12 , 17 21 , 23 , 25 , 28 ]; three were from Turkey [ 16 , 22 , 24 , 26 , 27 ], and one was from America [ 15 ]. Among the 17 studies, 11 studies included patients undergoing coronary angiography (CAG) or percutaneous coronary angiography [ 11 , 12 , 16 , 17 , 19 , 21 , 23 – 26 , 28 ], two included patients undergoing coronary artery bypass [ 22 , 27 ], one was related to pediatric severe sepsis [ 15 ], and three included patients with other diseases [ 10 , 18 , 20 ]. Malnutrition was mainly assessed using the CONUT score, geriatric nutritional risk index, Modified Nutrition Risk in Critically Ill Patients score, PNI, and NRS-2002.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The population of the original studies was mainly from China [ 10 12 , 17 21 , 23 , 25 , 28 ]; three were from Turkey [ 16 , 22 , 24 , 26 , 27 ], and one was from America [ 15 ]. Among the 17 studies, 11 studies included patients undergoing coronary angiography (CAG) or percutaneous coronary angiography [ 11 , 12 , 16 , 17 , 19 , 21 , 23 – 26 , 28 ], two included patients undergoing coronary artery bypass [ 22 , 27 ], one was related to pediatric severe sepsis [ 15 ], and three included patients with other diseases [ 10 , 18 , 20 ]. Malnutrition was mainly assessed using the CONUT score, geriatric nutritional risk index, Modified Nutrition Risk in Critically Ill Patients score, PNI, and NRS-2002.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, malnourished patients with CA-AKI had a significantly higher risk of all-cause mortality than patients with malnutrition. A multicenter prospective cohort of 2,083 patients undergoing PCI demonstrated that malnourished patients with CA-AKI had a higher risk of all-cause mortality than did those without [ 19 ]. Therefore, clinicians should assess and monitor the nutritional status of patients undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation